OPINI AUDIT GOING CONCERN: MENGURAI FAKTOR YANG MEMPENGARUHI - marhamah, Marhamah; Indriastuti, Ariyani (Sekolah Tinggi Ilmu Ekonomi Semarang, 2024)
A going concern audit opinion is issued by auditors to determine whether a company can sustain its operations. Auditors are responsible for evaluating whether there is significant doubt about the entity's ability to continue as a going concern. Research findings indicate that financial condition has a significant influence on the going concern audit opinion, whereas company size and auditor reputation do not have a significant impact. Auditors should consider management policies, auditor experience, and corporate governance factors when determining a going concern audit opinion.